FBXW2 suppresses breast tumorigenesis by targeting AKT-Moesin-SKP2 axis - Ganesh Kumar Barik; Osheen Sahay; Anindya Mukhopadhyay; Rajesh Kumar Manne; Sehbanul Islam; Anup Roy; Somsubhra Nath; Manas Kumar Santra (Cell Death and Disease, 2023)
Abstract Oncogene Moesin plays critical role in initiation, progression, and metastasis of multiple cancers. It exerts oncogenic activity due to its high-level expression as well as posttranslational modification in cancer. However, factors responsible for its high-level expression remain elusive. In this study, we identified positive as well as negative regulators of Moesin. Our study reveals that Moesin is a cellular target of F-box protein FBXW2. We showed that FBXW2 suppresses breast cancer progression through directing proteasomal degradation of Moesin. In contrast, AKT kinase plays an important role in oncogenic function of Moesin by protecting it from FBXW2-mediated proteasomal degradation. Mechanistically, AKT phosphorylates Moesin at Thr-558 and thereby prevents its degradation by FBXW2 via weakening the association between FBXW2 and Moesin. Further, accumulated Moesin prevents FBXW2-mediated degradation of oncogene SKP2, showing that Moesin functions as an upstream regulator of oncogene SKP2. In turn, SKP2 stabilizes Moesin by directing its non-degradable form of polyubiquitination and therefore AKT-Moesin-SKP2 oncogenic axis plays crucial role in breast cancer progression. Collectively, our study reveals that FBXW2 functions as a tumor suppressor in breast cancer by restricting AKT-Moesin-SKP2 axis. Thus, AKT-Moesin-SKP2 axis may be explored for the development of therapeutics for cancer treatment.